Evaluating Parents’ Concerns, Needs, and Levels of Satisfaction with the Services Provided for ASD Children in Saudi Arabia - Al Awaji NN; Al-Taleb SM; Albagawi TO; Alshammari MT; Sharar FA; Mortada EM (Journal of Multidisciplinary Healthcare, 2024)
Nisreen Naser Al Awaji,1 Sumaih Mohammed Al-Taleb,1,* Teef Olayan Albagawi,1,* Maram Taleb Alshammari,1,* Fay Abdullah Sharar,1,* Eman M Mortada2 1Department of Health Communication Sciences, College of Health and Rehabilitation Sciences, Princess Nourah bint Abdulrahman University, Riyadh, 11671, Saudi Arabia; 2Health Sciences department, College of Health and Rehabilitation Sciences, Princess Nourah bint Abdulrahman University, Riyadh, 11671, Saudi Arabia*These authors contributed equally to this workCorrespondence: Eman M Mortada, Health Sciences department, College of Health and Rehabilitation Sciences, Princess Nourah Bint Abdulrahman University, P.O Box 84428, Riyadh, 11671, Saudi Arabia, Email EMMortada@pnu.edu.saBackground: Supporting children with autism spectrum disorder (ASD) and their parents is vital in improving their children’s abilities and their parents’ ability to care for them. Thus, parents’ perceptions of and levels of satisfaction with the services provided for their children must be assessed.Aim: This study aimed to understand parents’ perceptions of and satisfaction with the speech–language services (SLS) provided for ASD children in different health facilities in Saudi Arabia.Methods: This cross-sectional study included 109 parents of ASD children. The survey included five sections dealing with (1) general information about the child; (2) assessment of the child’s ASD characteristics (including their age when diagnosed, when they first noticed symptoms, and their speech, language, and communication abilities); (3) the reasons for enrollment in SLS sessions; (4) questions about SLS; and (5) parents’ perceptions of SLS, satisfaction with the service, descriptions of their children’s progress, and the respect and support they received.Results: Parents’ satisfaction levels were significantly higher when they had easy access to SLS, sufficient information and support, proper training in applying therapy exercises at home, and perceived respect and support from speech and language pathologists (SLPs). The reasons for discontinuing SLS included high session costs, the need for initial behavioral sessions, the lack of qualified SLPs, the end of the sessions, the lack of improvement, the nonavailability of specialized centers, and parents’ dependence on home training only. They also sought opportunities for work and education, continuous and intensive SLS sessions, reduced costs, centers for adults with ASD, and accessible schools. Parents’ main concerns were their children’s poor speech and language skills, independence, and social acceptance.Conclusion and Implications: The study highlighted the importance of understanding parents’ experiences with SLS, identifying the factors that enhance SLS use by ASD children, and improving parents’ satisfaction with such services.Keywords: autism spectrum disorder, concerns, parents, perceptions, needs, speech language service